2004
DOI: 10.1128/iai.72.12.6939-6944.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity against Eimeria acervulina following In Ovo Immunization with a Recombinant Subunit Vaccine and Cytokine Genes

Abstract: A purified recombinant protein from Eimeria acervulina (3-1E) was used to vaccinate chickens in ovo against coccidiosis both alone and in combination with expression plasmids encoding the interleukin 1 (IL-1), IL-2, IL-6, IL-8, IL-15, IL-16, IL-17, IL-18, or gamma interferon (IFN-␥) gene. When used alone, vaccination with 100 or 500 g of 3-1E resulted in significantly decreased oocyst shedding compared with that in nonvaccinated chickens. Simultaneous vaccination of the 3-1E protein with the IL-1, -15, -16, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 49 publications
(69 reference statements)
2
51
1
Order By: Relevance
“…Therefore, with the progress of molecular biology, recombinant subunit vaccines or DNA vaccines that elicit specific immunity are eminently preferable as alternatives . Recent studies have demonstrated various levels of protection by vaccination with recombinant antigen or DNA vaccines (Ding et al , 2004Kopko et al 2000;Wu et al 2004;Xu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with the progress of molecular biology, recombinant subunit vaccines or DNA vaccines that elicit specific immunity are eminently preferable as alternatives . Recent studies have demonstrated various levels of protection by vaccination with recombinant antigen or DNA vaccines (Ding et al , 2004Kopko et al 2000;Wu et al 2004;Xu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-mediated immunity plays a key role in the protection against E. tenella in chickens, but the role of humoral immunity in E. tenella infected chickens is ambiguous (Jang et al 2010;Ding et al 2004;Wallach 2010;Abdul Hafeez et al 2006). Chickens in the subunit vaccine plus ginsomes groups had higher antibody titers than those of the subunit vaccine group before challenge.…”
Section: Discussionmentioning
confidence: 96%
“…Profilin is expressed in all sexual stages of E. tenella, stimulates cell-mediated immunity, and contains a putative conserved domain for the actin-regulatory protein profilin (Ding et al 2004;Jang et al 2010;Lee et al 2010b;Song et al 2000;Lillehoj et al 2000;Zhao et al 2011). In the present study, we investigated the adjuvant effect of ginsomes on the immune response and protection efficacy induced by recombinant profilin antigen plus ginsomes after oral infection with E. tenella sporulated oocysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ding et al (2004) concluded that it is possible to control this disease using maternal vaccines. Those authors claimed that the antibody transfer from mother to their progeny may be able to provide protection against clinic coccidiosis, reducing the incidence of macroscopic lesions and other clinical manifestations of this disease.…”
Section: ____________________________________________________________mentioning
confidence: 99%